Indoor Decontamination Textiles by Photocatalytic Oxidation: A Review - Hafeezullah Memon; Sohail Yasin; Nazakat Ali Khoso; Munir Hussain (Journal of Nanotechnology)
A large number of researches have been made to make the textile intelligent and smarter; this is achieved by imparting functionality to the textile materials. The indoor environment possesses a variety of pollutants which do not come from the outer environment, but they come from the inner environment itself. Today, the smarter fabrics that may clean the indoor air have been studied by various researchers. The smarter fabrics contain the nanocoating of semiconductor oxides, mostly TiO2; thus the synthesis and application of these nanoparticles on the textile material have been reviewed in this paper. Moreover, there are lots of environmental and health issues regarding nanoparticles that have also been discussed in brief.